Potensi Pengembangan Bus Pariwisata Bus Rapid Transit Kota Palangka Raya - Muhammad Betang Bagaskara; Sutan Parasian Silitonga; Ina Elvina (Fakultas Teknik, 2023)
Bus Rapid Transit (BRT) is a fast, convenient, safe and timely bus infrastructure, vehicle, and system in Palangka Raya City, Central Kalimantan, Indonesia. The emergence of Bus Rapid Transit (BRT) is something that is expected to be able to answer the needs of the community for the need for safe and comfortable tourism transportation. With the existence of Bus Rapid Transit (BRT) transportation, researchers conducted a study to find out the public's interest in Bus Rapid Transit (BRT) transportationin Palangka Raya City. This research was conducted by distributing questionnaires and interviews to 100 respondents. Data analysis with the SPSS program using the logit binary method. From this analysis we can see factors of public interest in using Bus Rapid Transit (BRT). Based on the results of research, people are interested in using Bus Rapid Transit (BRT) transportation. Based on the result of research, people are interested in using Bus Rapid Transit (BRT) transportation, which is influenced by vehicle ownership, experience using tourist buses within the city and frequency of travel in a month. Based on theresults of data analysis of tariff variables, it was found that 24% of the public disagreed if the tariff wasset and 76% of the public agreed if the tariff was set.